Protection of the Seas from Pollution by Vessel’s Sewage with Reference to Legal Regulations - Koboević, Žarko; Komadina, Pavao; Kurtela, Željko (Promet - Traffic&Transportation, 2012)
This paper deals with the rules and regulations pertaining to the protection of the marine environment from the pollution by vessel’s sewage. There is an international perspective on legal regulations dealing with this matter, but the sensitive marine environment has not been properly covered. Some maritime countries have set forth their own and more strict regulations to provide for a more efficient protection of their marine environments. Having compared the international legal regulations for the protection of the seas from pollution by vessel’s sewage with the regulations of individual countries that have stricter regulations, a certain similarity has been noticed in some criteria, but also significant differences in some other criteria concerning allowed discharge of treated or untreated waste waters from the vessels. Amendments to the valid legal regulations and establishment of new rules pertaining to the marine environment are of particular importance in order to provide for a more effective protection of the seas from the increasing pollution from vessel’s sewage preventing thus the negative influence onto marine organisms, human health and economy.KEY WORDS: sea pollution, sewage, black water, faecal coliform bacteria, suspended solids, sewage treatment plant, convention